From Disorder to Order - Xiao-Guang Yue; Yong Cao; Michael McAleer (Tinbergen Institute, 2015)
In the physical sciences, order and disorder refer to the presence or absence of some symmetry or correlation in a many-particle system. It follows that it is important to examine whether there is any regularity hidden in the phase transition of the disorder-order relationship. In this paper a series of experiments are devised and executed to reveal the power law relationship between order and disorder, and to determine that the power law is indeed an important regular pattern in the phase transition from disorder to order.
Keywords: C12; C18; C92; 330; Order; disorder; power law; scale invariance; symmetry; regularity; physical sciences